Assessment of Drug Related Problems in Stroke Patients Admitted to a South Indian Tertiary Care Teaching Hospital - A.T, Celin; J, Seuma; A, Ramesh (Indian Journal of Pharmacy Practice)
Introduction: Drug related problems contribute to patient's morbidity, mortality and decreased quality of life. Drug related problems can occur at any stage of prescribing, transcribing, dispensing and administration of medications. Identifying and resolving the drug related problems will improve the patient's safety and therapeutic outcomes. Objective: To study the rate, types, pattern, and clinical significance of drug related problems in stroke patients. Methodology: A prospective study was conducted in the medicine and neurology wards of a tertiary care hospital over a period of six months from November 2011 to April 2012. Necessary demographic and clinical data was collected from the case records. The treatment data was analyzed to determine the rate, pattern, clinical significance, and outcomes of DRPs in stroke patients. Results: Atotal of 80 DRPs were identified in 108 patients. The frequency of drug related problems was 1.54 per patient. The highly reported drug related problem was drug interactions (25.0%) followed by drug use without indication (15.0%) and adverse drug reactions (15.0%). Majority interventions (97.9%) were accepted by the health care professionals. Conclusion: Early detection and intervention of drug related problems may improve the therapeutic outcomes in stroke patients. Developing and adopting policies regarding the drug administration, dispensing and prescribing would minimize the drug related problems in stroke patients.
Keywords: Drug related problems; Stroke; Clinical Pharmacist